STUDY OF SEISMIC EFFECTS ON CHANGES IN GROUNDWATER PRESSURE: EQUIPMENNT AND SOME WELL OBSERVASTION RESULTS FOR THE KAMCHATKA PENINSULA - S. V. Boldina; G. N. Kopylova; V. A. Kobzev (Геодинамика и тектонофизика, 2022)
The relevance of the work is determined by the necessity to develop the hardware part of the seismic subsystem of the Large-Scale Research Facilities functioning at the Federal Research Center of the Geophysical Survey of the Russian Academy of Sciences to study seismic signals in groundwater pressure changes. For this purpose, the well monitoring on the territory of the Petropavlovsk-Kamchatsky test site, Kamchatka Peninsula, was updated using Keller equipment, Switzerland (sensors of PAA36 XiW CTD Si, PAA36 XiW modifications, data logger GSM-2), Campbell Scientific Inc, USA (CR6 and CR1000 data loggers) and a budgetary hydrogeodynamic data recorder (HDDR) based on the STK-1 minicomputers, created at the Kamchatka Branch of the GS RAS. A description has been provided concerning the sets of digital equipment installed in four wells for precise recording of groundwater pressure variations with a frequency of 20.00–0.08 Hz. Consideration is being given to the characteristics of the equipment installed in individual wells and to the problems solved in the process of updating the well observation system in order to study vibration effects and hydrogeodynamic precursors of earthquakes. The paper presents the newly obtained results of recording the high-frequency variations in groundwater pressure in wells during the 2020–2021 local and remote earthquakes. A discussion is provided of new possibilities for studying vibration effects on changes in ground water pressure with a frequency comparable to the frequency of recording seismic events by seismometric equipment. Using a new equipment for recording water pressure in the unique well E-1 made it possible to record, a hydrogeodynamic precursor in real time before the March 16, 2021, Mw=6.6 earthquake which occurred at the epicentral distance of 350 km from the well.